2012
DOI: 10.1016/j.annepidem.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Breast Cancer in Families with Cleft Lip and Palate

Abstract: PURPOSE To test whether females in families with cleft lip and/or palate (CL/P) have increased breast cancer risk METHODS Using the Danish Facial Cleft Registry, females with CL/P, mothers of children with CL/P, and sisters to CL/P cases were identified for the Danish birth cohorts 1911 to 1975. These females were compared to a 5% random sample of these cohorts regarding the incidence and age of onset for breast cancer registered in the Danish Hospital Discharge Register 1977–2005. RESULTS Examining 48,404… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 46 publications
0
35
0
1
Order By: Relevance
“…Data from Denmark initially suggested that NSCL/P in females may increase the risks for breast cancer [Bille et al, 2005], although this suggestion was not confirmed in a later study [Dietz et al, 2012]. Family data from Pittsburgh, US, showed that families with individuals born with NSCL/P report breast cancer more often than families without babies born with birth defects, including oral clefts [Menezes et al, 2002].…”
Section: To the Editormentioning
confidence: 96%
“…Data from Denmark initially suggested that NSCL/P in females may increase the risks for breast cancer [Bille et al, 2005], although this suggestion was not confirmed in a later study [Dietz et al, 2012]. Family data from Pittsburgh, US, showed that families with individuals born with NSCL/P report breast cancer more often than families without babies born with birth defects, including oral clefts [Menezes et al, 2002].…”
Section: To the Editormentioning
confidence: 96%
“…Similarly, the risk of breast cancer in families with patients affected by NSCL/P was not increased. 9 On the other hand, a study showed a family history of cancer (colon, brain, leukemia, breast, prostate, skin, lung and liver) more often in relatives of NSCL/P compared to the control group. Recently, we evaluated the risk of NSCL/P in relatives of women with breast cancer in the Brazilian population and found no association between the two conditions.…”
Section: Discussionmentioning
confidence: 99%
“…7 The association between cancer and NSCL/P could be attributable to both genetic factors and/or familial environmental factors that are both teratogenic and carcinogenic. 9 Another possibility could be that having a cleft leads to social marginalization and changes in lifestyle that may be predisposed to an individual and their family to cancer (i.e. smoking, high alcohol use, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from different countries (USA, Latvia, Denmark, and Brazil) have identified an association between cleft palate and cancer [90][91][92][93][94][95]. The first epidemiological studies addressed the presence of cancer in cleft lip/palate subjects and their families.…”
Section: Cleft Palate and Cancermentioning
confidence: 99%